CNTs anchored on defective bimetal oxide NiCoO2-x microspheres for high-performance lithium-ion battery anode. (10th September 2020) - Tang, Hong; Jiang, Mengjin; Zhang, Yue; Lai, Xiaoxu; Cui, Ce; Xiao, Hongyan; Jiang, Shouxiang; Ren, Erhui; Qin, Qin; Guo, Ronghui
Abstract: Bimetal oxides are widely used in the field of lithium ion storage because of their high theoretical capacity. However, the capacity of the bimetal oxides decays sharply due to its poor electrical conductivity. Herein, a novel oxygen vacancy defect bimetal oxide NiCoO2-x @CNTs composite with carbon nanotubes (CNTs) anchored on defective NiCoO2-x microspheres was prepared toward enhancement of lithium ions storage. The defective NiCoO2-x microsphere improves electrical conductivity and accelerates lithium ion transfer. The microspheres have abundant mesopores to shorten the diffusion path of lithium ions and accommodate volume fluctuation. In additional, CNTs anchored on NiCoO2-x microspheres further enhance structural stability and electrical conductivity. NiCoO2-x @CNT electrodes exhibit excellent electrochemical performance with good rate capability (521.9 mA h g −1 at 5 A g −1 ) and outstanding long-cycle stability (965 mA h g −1 at 0.1 A g −1 over 155 cycles, 1114.3 mA h g −1 at 0.5 A g −1 over 360 cycles, 618.4 mA h g −1 at 1 A g −1 over 400 cycles and 520 mA h g −1 at 5 A g −1 over 400 cycles) when NiCoO2-x @CNT is employed as a lithium-ion battery anode. This defective material design strategy provides an effective way for improving lithium ion storage. Graphical abstract: Image, graphical abstract